The Effect of Applying Index Card Match (ICM) Active Learning Strategy on Student Learning Outcomes in Information and Communication Technology Subjects in Class IX of SMP Negeri 19 Padang - Bimas Saputra, Ebit; Andika, Rido (Siber International Journal of Education Technology (SIJET), 2023)
This study aims to determine the effect of student learning outcomes by using an Active Learning strategy type index Card Match (ICM) on ICT learning outcomes for class IX Negeri 19 Padang students. This research is in quantitative form with a quasy experimental approach. The type of data in this study is in the form of student learning outcomes and the data source is student scores. Then the data is processed using the T-Test. Based on the research results, the average value of the experimental group with the ICM strategy was obtained 80 .70 , higher than the average value of the control group 63.83 . The calculation of the t-test states that t count is 5.57 while t table = 2.0 0 , t.count > t.table. This means that there is a significant difference in the learning outcomes of class students who use the Active learning strategy of the Index Card Match (ICM) type (experimental class) with the learning outcomes of class students who use conventional strategies (control class).